PRIMJER TRODIMENZIONALNE ANALIZE U TENISU - Branimir Mikić; Grujo Bjeković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
3D techniques as biochemical models are successfully used in sports. Scientists in cooperation with couches are, more and more, using technical possibilities in 3D analysis to improve sportsmen results. The objective of this analysis is an attempt to classify the movements in tennis and to stabile morph kinetic sequences in teaching and training. Basic thing in the usage of biomechanical models is to use 3D techniques successfully as a supplement to the sport. Observation and description of the parameters of weather and space were constant occupation of couches. However, to examine performance without interference into the competition or training, it is necessary to use new technical and methodological approach. With the help of several examples we will illustrate the potential of 3D qualitative analyses - methodological principals and temporary limitation and necessary corrections; analyzing, within the framework of teaching, the basic strikes in tennis.